42+3y-14=12y-14-3y

Simple and best practice solution for 42+3y-14=12y-14-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42+3y-14=12y-14-3y equation:



42+3y-14=12y-14-3y
We move all terms to the left:
42+3y-14-(12y-14-3y)=0
We add all the numbers together, and all the variables
3y-(9y-14)+42-14=0
We add all the numbers together, and all the variables
3y-(9y-14)+28=0
We get rid of parentheses
3y-9y+14+28=0
We add all the numbers together, and all the variables
-6y+42=0
We move all terms containing y to the left, all other terms to the right
-6y=-42
y=-42/-6
y=+7

See similar equations:

| 8=8(w+4)-2w | | x​2​​+3x−10=0 | | (2+5x)-10=-22+6x | | X+1=-5+2x | | 7/2x=28/2 | | 5x+4=2×+1 | | 49=1x+1+3x | | 5x4=15x3 | | 2/5x=8/25 | | -9-3x;x=5 | | 8y-8=37-7 | | 6^x=5 | | x+18+4=-43-4x-47 | | (2x-4)^2=21 | | 3(x+17)=9+2x | | 16w=81+7w | | 6+n+4-2=8+4n | | x/2=210 | | x*12=16(x-2) | | 2x+8=9x+8 | | 3/5=4/a | | -7.3=11+a(9.3) | | 12x+7;x=-2 | | 32+7r=8(3r+4) | | 21=3-3(x+4) | | -2(2x−4)+3=6x+1 | | (7x+1)(x-1)-43+48=0 | | 10+x=210 | | 16x+14=9x | | 7x+-3=7x+7 | | (6m-3)(m2+5m+2)=0 | | 7x−3=3x−35 |

Equations solver categories